Blood lactate thresholds and walking/running economy are determinants of backpack-running performance in trained soldiers. (January 2017) - Simpson, Richard J.; Graham, Scott M.; Connaboy, Christopher; Clement, Richard; Pollonini, Luca; Florida-James, Geraint D.
Abstract: We developed a standardized laboratory treadmill protocol for assessing physiological responses to a simulated backpack load-carriage task in trained soldiers, and assessed the efficacy of blood lactate thresholds (LTs) and economy in predicting future backpack running success over an 8-mile course in field conditions. LTs and corresponding physiological responses were determined in 17 elite British soldiers who completed an incremental treadmill walk/run protocol to exhaustion carrying 20 kg backpack load. Treadmill velocity at the breakpoint (r = −0.85) and Δ 1 mmol l −1 (r = −0.80) LTs, and relative V ˙ O 2 at 4 mmol l −1 (r = 0.76) and treadmill walk/run velocities of 6.4 (r = 0.76), 7.4 (r = 0.80), 11.4 (r = 0.66) and 12.4 (r = 0.65) km h −1 were significantly associated with field test completion time. We report for the first time that LTs and backpack walk/run economy are major determinants of backpack load-carriage performance in trained soldiers. Highlights: The physiological determinants of backpack running performance remain undefined Physiological data on elite British soldiers are reported Laboratory data can be used to predict backpack-running performance in the field Backpack load carriage success is dependent on blood lactate threshold and economy